Emerging sectarianism in the Dead Sea scrolls continuity, separation, and conflict - Collins, John J. 1946-; Geyser-Fouché, Ananda (Brill, 2022)
"These essays reflect the lively debate about the sectarian movement of the Scrolls. They debate the degree to which the movement was separated from the rest of Judaism, and whether there was one or several watershed moments in the separation. Notable contributions include a cluster of essays on the Teacher of Righteousness and a thorough survey of the archaeology of Qumran. The texts are problematic in historical research because they rely on biblical stereotypes. Nonetheless, possible interpretations can be compared and degrees of probability debated. The debate is significant not only for the sect but for the nature of ancient Judaism"
Includes bibliographical references and index
Keywords: Qumrantexte; Qumrangemeinde; Dead Sea scrolls; Qumran community; Konferenzschrift -- 2021